Teaching clinical hematology and leukocyte differentiation in veterinary medicine using virtual patients - Hannah Marahrens; Matthias Gerhard Wagener; Elisabeth Schaper; Jana Zintl; Frederik Kiene; Martin Ganter (Frontiers in Veterinary Science, 2023)
Due to contact restrictions imposed because of the COVID-19 pandemic, we created a novel digital course on the Moodle learning platform for winter term in 2020. In the clinical pathology course (CPC) with hematological content, third-year students were able to work independently on 10 extra digital cases of internal medicine involving eight different animal species as a compensation for the reduction in traditional microscopy exercises. Each case presented was initiated using an anamnesis, also the participants to generate a differential blood count based on digitized leukocytes, previously been photographed using a microscope camera. The cases were successive and increased in complexity, for example through the increase in the number of different cell types to be differentiated. The participants had the opportunity to evaluate the course through a final module to rate user-friendliness and acceptance. The total results of the participants in 2021 were analyzed descriptively, focusing on success rates, time spent on the tasks, and number of attempts. A total of 237 (= 96%) of 247 students completed all cases, each assessing 1033 photographed blood cells in sum. The mean processing time was 22.48 min for a differentiation and the students spent an average of 1.48 attempts on it. A voluntary feedback form was completed by 192 (= 78%) students, with more than 95% rating the course positively in 12 evaluation questions, and 29 of 33 comments (= 87.88%) providing positive statements in a comment box. Suggestions for improvement primarily included more explanations on erythrocyte morphologies, followed by adjusting the difficulty level and improving the presentational set-up. Slight improvements in results, time spent on processing the tasks, and the number of attempts indicated an achievement of routine and confidence during the course and were associated with an increase of competency. The positive feedback showed a high acceptance of the digital format and students evaluated the course as improving the quality of teaching when combined with practical exercises.